Machinability Analysis of SUH 35 Material Subjected to Annealing Process on Engine Valve Making Surface Grinding - Arief, Sulaiman; Fitri, Muhamad (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
Steel has various physical and mechanical properties. The very high hardness of steel makes it difficult to form or process with a machine. Based on these problems, there needs to be a treatment (treatment) that can improve the mechanical properties of steel. The annealing process is the process of heat treatment of metals or alloys by heating the metal to austenite temperatures, holding it at that temperature for a while, and cooling the metal at a very slow cooling rate. The heat treatment process aims to improve the mechanical properties of the metal or alloy. In this study, SUH 35 steel was used as the test material. Eight test materials are prepared, namely four materials Unannealed and four materials treated with annealing. Annealing specimens are given heat treatment with a temperature of 750 ° C ± 10 ° C with a holding time of 60 minutes. This specimen is carried out by turning process with variable machining feeding that varies 0,25 mm/revolution, 0.50 mm/revolution, 0,75 mm/revolution, and 1 mm/revolution. The results of this study show that the annealed material has a lower roughness value of 311.49 VHN. In comparison, the Unannealed sample has a hardness value of 607.59 VHN, which shows better machinability in the annealed material. The results of the feeding variation show that the greater the feeding value, the more it will affect the increase in the roughness, resulting in the surface grinding process.